Performance simulation of a double-reheat Rankine cycle mercury turbine system based on exergy - Gonca, Guven; Genc, Ibrahim (INDERSCIENCE ENTERPRISES LTD, 2019)
In this paper, a performance investigation of a Rankine cycle mercury turbine system operating with methane and including two closed feed mercury heaters, one open feed mercury heater and three turbines is comprehensively performed. The most known performance specifications such as ecological coefficient of performance, exergy efficiency, exergy destruction, net power and net power density, and are utilised to examine and optimise the performance of the system. The influences of boiler and condenser temperatures, the first and second reheat stage temperatures, extracted mercury temperature on the performance properties of the system have been comprehensively investigated. Beside the mathematical model investigated in the paper, an artificial neural network (ANN) model is also presented and it is shown that a good approximation is computed with only five parameters.
Keywords: mercury turbine; optimisation; reheated Rankine cycle; ECOP; exergy; ANN model; FLUID SELECTION; ENERGY; OPTIMIZATION; DESIGN; SINGLE; WATER; Thermodynamics; Energy & Fuels